An Act to Establish, for the Purpose of Implementing Any Order Issued by the President for Fiscal Year 1986 Under Any Law Providing for Sequestration of New Loan Guarantee Commitments, a Guaranteed Loan Limitation Amount Applicable to Chapter 37 of Title 38, United States Code, for Fiscal Year 1986. (1986)
Summary goes here